Hafted Tool-use Experiments with Australian Aboriginal Plant Adhesives: Triodia Spinifex, Xanthorrhoea Grass Tree and Lechenaultia divaricata Mindrie - V. Rots (EXARC, 2020)
Hafted stone tools commonly figure in Australian archaeology but hafting traces and manufacture processes are infrequently studied. The Aboriginal processing of resin from Xanthorrhoea (Sol. Ex Sm.) grass tree, Triodia (R.Br.) spinifex and Lechenaultia divaricata (F.Muell.) mindrie, is reported with experiences and observations about the performance of resin mixtures in hafted tool-use experiments. Pure mixtures of winnowed Triodia grass, though soft, were more effective as a sticky adhesive than lumps collected from ant nests or the ground following bushfires. Xanthorrhoea resin mixed with kangaroo dung and charred wood was effective, though brittle, and re-heating made it less sticky and more brittle. Mindrie root mixed with kangaroo dung and ashes proved highly effective. Triodia, Xanthorrhoea and Lechenaultia resins have different adhesive properties, and the resin sources, additives and processing techniques all affect how and when hafts break.